Helios Pharmacy - Edwards, Penny (Homœopathic Links, 2015)
Around the world there are many homeopathic pharmacies. Some are very old; some new. Some are big; some small. In a series of articles we intend to bring some special pharmacies into the limelight. Readers are welcome to suggest other pharmacies to be featured. This article presents Helios Pharmacy in the United Kingdom.
Keywords: Homeopathic pharmacy; History; LM potencies; Q potencies